Chapter I gesuati farmacisti di Lucca - Gagliardi, Isabella (Fragmentaria. Studi di storia culturale e antropologia religiosa, 2020)
The essay constitutes the historical premise for the contribution of Marco Biffi, dedicated to the pharmacological Jesuat manuscript (1562), and it describes the context in which was produced this manuscript, the most important pharmacological codex of the Jesuats: San Girolamo in Lucca. Is investigate the identity of the authors of the codex, which is briefly described, and the importance of scientific studies and the practice of distillation and pharmacology among the Jesuats.